Biology of Copturomimus hustachei Kissinger, 1957 (Coleoptera: Curculionidae), a stem and branch borer of avocado (Persea americana) in Colombia - Moreno-Gaviria, Julián; Díaz-Grisales, Valentina; Carabalí-Muñóz, Arturo (Revista Colombiana de Entomología, 2023)
The genus Copturomimus Heller, 1895 is distributed in Brazil, Colombia, Costa Rica, Guatemala, Honduras, Mexico, and Panama, and includes some species that in their larval stage bore into stems and branches of Persea americana Mill. In Colombia, the associated species to the damage of avocado stems and branches in commercial crops and nursery plants has traditionally been identified as Copturomimus perseae Hustache, 1947; however, the valid name of the species is Copturomimus hustachei Kissinger, 1957. In order to update the information on this species in Colombia, the biological cycle on branches of avocado cv. Lorena was determined, and its habits and developmental stages were described. The total time from egg to adult emergence was 86.78 ± 25.41 days. The duration of developmental stages was 9.29 ± 1.22 days for the egg, 66.18 ± 10.86 days for the larval development and 13.08 ± 3.99 days for the pupa; adult longevity ranged between 15 and 49 days. Description of the habits, developmental times of the biological cycle and photographic documentation provided can contribute to improve the diagnosis of C. hustachei to generate management schemes for its populations in avocado crops.